2021
DOI: 10.3846/jcem.2021.13754
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Emotions and Public Acceptance of Recycled Water for Urban Residents

Abstract: Worldwide water scarcity has prompted governments to develop alternative water resources, and public acceptance plays a critical role in the implementation of recycled water projects. The aim of this study was to explore how public acceptance can be affected by people’s emotional responses to recycled water. In study 1, the general population was divided into four groups, clustering analysis with the intensity of various emotions was conducted, and the association between emotions and acceptance was explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Previous studies have investigated the relationship between self-perceived knowledge level and acceptance and concluded that greater knowledge or awareness is associated with increased recycled water acceptance [34,35]. Public acceptance is also influenced by other people's opinions, social norms, information disclosure, and other external context factors [36][37][38]. Previous studies have found that environmental education and publicity or disclosure of water information from authorities or the media can influence the acceptance of recycled water [35,39].…”
Section: Predictors Of Recycled Water Use Behaviormentioning
confidence: 99%
“…Previous studies have investigated the relationship between self-perceived knowledge level and acceptance and concluded that greater knowledge or awareness is associated with increased recycled water acceptance [34,35]. Public acceptance is also influenced by other people's opinions, social norms, information disclosure, and other external context factors [36][37][38]. Previous studies have found that environmental education and publicity or disclosure of water information from authorities or the media can influence the acceptance of recycled water [35,39].…”
Section: Predictors Of Recycled Water Use Behaviormentioning
confidence: 99%
“…En cuanto al aspecto funcional relacionado a la temática de este trabajo [2] , [9], [10] y [11] se menciona que el diseño del inodoros con separador de orina se acepta cuando se evidencian otros beneficios como ahorro del agua y reutilizar la orina como abono, mientras que en cuanto a la percepción formal, existen investigaciones que describe como se implementa y se acepta de parte de los encuestados, el inodoro mejorado adaptado a la posición de cuclillas [2], debido a la inclusión de un aspecto cultural en la forma externa del diseño, que es la porcelana blanca imitando la vasija oriental de la Dinastía Yi coreana, lo cual hizo que tenga altos niveles de preferencia debido a la integración de esta característica cultural ancestral en su diseño. El antecedente que tiene un mecanismo similar al propuesto en esta investigación [12] tiene aceptación en contextos socio-culturales de pobreza.…”
Section: Introductionunclassified
“…Hess, David J investigated the utilization degree mode of two main indirect uses of circulating water: double network system and groundwater recharge [4]. Ding, Yizhe analyzed the relationship between urban residents' feelings for reclaimed water and public acceptance [5]. Greenaway, Tameika's research found that positive emotional information framework could reduce risk perception and improve acceptance of circulating water [6].…”
Section: Introductionmentioning
confidence: 99%